Life negative events and depressive symptoms: the China longitudinal ageing social survey - Wang, Zhenjie (BMC Public Health, 2020)
BACKGROUND: Although some studies have reported the association between life negative events and depressive disorders, very limited studies have examined the association between life negative events exposure and depressive symptoms risk among Chinese older adults. METHODS: Data were obtained from the China Longitudinal Ageing Social Survey (CLASS), which was a stratified, multi-stage, probabilistic sampling survey, conducted in 2014. General linear regression and logistic regression were used to examine the association between life negative events exposure and depressive symptoms among Chinese older adults. RESULTS: Life negative events showed statistical dose-response association with depressive symptoms risk after adjustment for the confounding factors (P(trend) < 0.001). Under consideration of life negative events exposure, participants who lived in rural areas, without a spouse or live alone were vulnerable to depressive symptoms. CONCLUSIONS: Life negative events played a risk role of depressive symptoms among Chinese older adults, especially among those in rural areas, females or without a spouse. Our current study is valuable for the development of special prevention depressive symptoms programs among elderly individuals, especially those who have experienced negative events.